2015
DOI: 10.1161/jaha.114.001575
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Controlled Case‐Series Study to Verify the Effect of Adherence to Beta‐Blockers in Secondary Prevention of Myocardial Infarction

Abstract: Background--Beta-blockers (BB) are recommended in secondary prevention of acute myocardial infarction (AMI), but adherence to prescription medication is a recognized problem. Most literature on the consequences of poor adherence to prescribed BB is limited by the possibility of "healthy adherer bias" and better-designed studies have been advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Many other studies of the effect of medications on cardiovascular outcomes also have mentioned on this phenomenon. A study reported that a healthy adherer effect might partially lead to overestimation of beta-blockers’ true effects on the reduction of cardiovascular risks [ 7 ]. A retrospective cohort study on the effects of statin adherence concluded that the healthy adherer effect made some contributions to reduced occurrence of primary cardiovascular events among women [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies of the effect of medications on cardiovascular outcomes also have mentioned on this phenomenon. A study reported that a healthy adherer effect might partially lead to overestimation of beta-blockers’ true effects on the reduction of cardiovascular risks [ 7 ]. A retrospective cohort study on the effects of statin adherence concluded that the healthy adherer effect made some contributions to reduced occurrence of primary cardiovascular events among women [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the observed proportion of cases with Y = y total number of AMI episodes, as reported in Di Bartolomeo et al 14 Given an observed P(Y = 1 | Y > 0) = 0.877 and Equation ( 4), we get Λ = 0.26 and recommend using W = Λ × 10 ≈ 3 partitions. Di Bartolomeo et al 14 reported around 1400 AMI episodes out of a cohort of roughly 30 000 individuals at risk in the population, producing a crude incidence rate of Λ ≅ 0.05. Following Whitaker et al's recommendation, Λ = 0.05 < 0.1 indicates a rare event and would have been expected to yield an acceptable level of bias in first event analysis.…”
Section: Example With Beta-blockers and Acute Myocardial Infarctionmentioning
confidence: 86%
“…3,4 However, this assumption is violated in the presence of event dependence, where the occurrence of an event influences the probability and timing of subsequent events and can lead to biased estimates of the exposure RI. Event dependence is suspected in many medical outcome events in SCCS studies, including stroke, 9,11,13 acute myocardial infarction, 10,11,14 and venous thromboembolism. 15,16 When event dependence is present or suspected in an SCCS study, investigators are typically advised to use first event analysis, which only includes the first outcome event for each case in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the authors found that adherence to dual antiplatelet therapy, ACEI/ARB and beta‐blockers was not significantly associated to lower risk of MACE 20 . However, a meta‐analysis of nearly 200 000 patients concluded that there was no association between beta‐blockers and all‐cause mortality, 36 but in other study found that being adherent to beta‐blockers was associated with a 20% reduction of recurrent AMIs 37 …”
Section: Discussionmentioning
confidence: 99%